COMPARISON OF MAXIMAL OXYGEN CONSUMPTION, RESTING METABOLIC RATE AND BODY COMPOSITION ANALYSIS BETWEEN AEROBIC AND ANAEROBIC SPORTS - Mihaela Nestorova Brazhanska; Dejanova, Beti; Karagjozova, Ivanka; Spirkoska Vangelovska, Biljana (ANTHROPOLOGICAL SOCIETY OF SERBIA, 2023)
The aim of this study is to compare the values of maximal oxygen consumption (VO2 max), resting metabolic rate (RMR) and body composition analysis between aerobic and anaerobic sports. 90 male athletes (25,34 ±5,6 age; 179,78±6.9 height/cm; 78,66±6,9 weight/kg and 24,34±2,75 BMI/ kg/m2) were tested for this study. The athletes were divided in 2 groups, I group- aerobic sports (endurance) (n=63), II group- anaerobic sports (strength) (n=26). Height was measured with stadiometer - СЕКА, body composition by means of bioelectrical impedance analysis - InBody 720, (Great Britain), RMR with indirect calorimetry- Fit Mate, COSMED, (Italy) and VO2 max with ergometric test Bruce on treadmill (ergo _run medical_α 24). Results showed that anaerobic athletes have significantly higher values of weight (83 ± 12kg) , BMI (26 ± 3 kg/m2) and body fat percentage-PBF (15 ± 8%), compared to aerobic athletes: weight (76 ±7 kg), BMI (23±1,5 kg/m2) and PBF (12 ±3 %). Aerobic athletes have significantly higher values skeletal muscle mass percentage -SMM (50 ±2%) and VO2 max (50,1 ± 4 ml/kg/min) (p<0,05) and higher values of RMR (2265 ±276 kcal/day) compared to anaerobic athletes: % SMM (48 ± 4%), VO2 max (45,9± 5 ml/kg/min) and RMR (2258 ± 314 kcal/day).Kako bi postigli više vrednosti VO2 max i bolju performasnu sportisti kombinuju submaksimalne i maksimalne trenažne sesije. To keep high SMM, endurance athletes need to have higher calorie intake. To achieve higher VO2 max values and better performance athletes tend to have combined submaximal and maximal training sessions.
Keywords: sports; body composition; resting metabolic rate; maximal oxygen consumption